Controllable Goos–Hänchen shift and optical switching in an Er3 + -doped yttrium aluminum garnet crystal. (19th March 2021) - Chen, Xiu-Mei; Shui, Tao; Meng, Chun; Zhang, Tong; Deng, Xu; Yang, Wen-Xing
Abstract: We propose an efficient scheme to control Goos–Hänchen (GH) shifts of the reflected and transmitted beams in a cavity containing Er 3 +  -doped yttrium-aluminum-garnet (YAG) crystal with a four-level Er 3 +  ionic system. It is found that both the values and signs of the reflected and transmitted GH shifts can be coherently controlled by tuning the relevant optical parameters, such as the incoherent pumping rate, and the intensity and detuning of the driving field. Furthermore, we propose a scheme for such a configuration of the reflected GH shift as a family of reflection-type optical switchings. It is shown that the average port spacing and reflectivity of the optical switching can reach approximately 1.03 mm and 16.88, respectively, which indicate the high performance of switching function. Our proposal may provide a possibility to implement optically tuned optical switching.